Dinâmica populacional de ovos e lagartas e parasitismo de ovos de Curuquerê-do-algodoeiro por Trichogramma pretiosum em cultivares convencionais e transgênica de algodoeiro - Costa, Lilian Lucia [UNESP]; Martins, Bruno Campos; Funichello, Marina [UNESP]; Busoli, Antonio Carlos [UNESP] (Universidade Federal de Uberlândia (UFU), 2011)
The introduction of new cotton cultivars in the Midwest region of Brazil resulted in a significant increase in productivity, but the use of inappropriate farming techniques brought many problems to field, as the higher incidence of pests, diseases and weeds. The aim of this work was to study the population dynamics of eggs and larvae of cotton leafworm and natural egg parasitism of the pest by Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) at different phenological stages of conventional and transgenic cultivars (Bollgard I) of cotton was carried out this experiment from December 2007 to April 2008 in Ipameri, Goias State, Brazil. The experimental design was a randomized blocks with five trataments and four replications. The treatments consisting of the conventional cotton cultivars DeltaOPAL, FMX 966, FMX 993, FMX 910 and the cultivar transgenic NuOPAL. Allabama argillacea Hubner (Lepidoptera: Noctuidae) oviposited on all cultivars, not presented differences in relation to oviposition preference. Compared to the average number of eggs of A. argillacea parasitized by T. pretiosum, there were no differences between cultivars. In conventional cultivars, small, medium and large larvae occurred from 34 days after plant emergence until the end of the cycle, while in the transgenic cultivar were found only small caterpillars. Cultivar NuOPAL control cotton leafworm since the first larval stage, and does not interfere in egg parasitism by T. pretiosum compared with other cultivars.

Com o objetivo de estudar a flutuação populacional de ovos e lagartas do curuquerê-do-algodoeiro e o parasitismo natural dos ovos da referida praga por Trichogramma pretiosum Riley (Hym.: Trichogrammatidae), em diferentes estágios fenológicos de cultivares convencionais e transgênica (Bollgard I) de algodoeiro, foi realizado um experimento no período de dezembro de 2007 a abril de 2008, em Ipameri, GO. O delineamento experimental utilizado foi o de blocos ao acaso, com cinco tratamentos e quatro repetições. Os tratamentos foram constituídos pelas cultivares convencionais DeltaOPAL, FMX 966, FMX 993; FMX 910 e a transgênica NuOPAL. Alabama argillacea (Hübner) (Lep.: Noctuidae). ovipositou em todas as cultivares, não havendo diferenças em relação à preferência para oviposição. Em relação ao número médio de ovos de A. argillacea parasitados por T. pretiosum, também não houve diferenças entre as cultivares. Nas cultivares convencionais, lagartas pequenas, médias e grandes ocorreram a partir dos 34 dias após a emergência das plantas até o final do ciclo, enquanto na cultivar transgênica foram encontradas apenas lagartas pequenas. A cultivar NuOPAL controla lagartas do curuquerê-do-algodoeiro desde os primeiros ínstares larvais, ou seja, ainda pequenas, e não interfere no parasitismo de ovos por T. pretiosum em relação as demais cultivares.
Population dynamics and track of eggs and egg parasitism of cotton leafworm by Trichogramma pretiosum cultivars in transgenic and conventional cotton
Keywords: Alabama argillacea, Gossypium hirsutum; Genetically modified organism; Trichogrammatidae